Tantangan Guru dalam Meningkatan Mutu Pendidikan Agama Islam Di Era Melenial - Anggun Wulan Fajriana; Mauli Anjaninur Aliyah (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
A process of education and learning requires an expert who is usually called an educator or teacher. Teachers or educators are not only obliged to transform science but also guide the development of students' morals and spirituality. Teachers must have a competency because competence is a combination of knowledge, skills, values, and attitudes reflected in the habit of thinking and acting. Therefore this study aims to determine the challenges of teachers to improve the quality of Islamic religious education (Pendidikan Agama Islam: PAI) in this millennial era. This study uses qualitative research with descriptive types and with case studies of data collection. The challenges of education in the millennium era faced by teachers in the form of Digital Literacy, Teachers as lifelong learners, Presenting Exciting and Meaningful Learning, Teachers must be exemplary, because the change in students in the millennial era teachers must see this challenge as positive with always make innovations and skills in learning that are in accordance with the demands of the times. criteria for professional PAI teachers, their professionalism is not only oriented to the material but also directed at spiritual orientation. Because professional PAI teachers are expected to be able to drive the progress of the people, especially in this millennial era. Based on the challenges faced by millennial teachers, PAI teacher professionalism is needed to help improve the quality of education.